Pengaruh Media Spinning Wheel Game Terhadap Pengetahuan Tentang Kesehatan Gigi Siswa/I Madrasah Ibtidaiyah Negeri 1 Kota Bengkulu Tahun 2020 - Darmawan, Rizqi (Poltekkes Kemenkes Bengkulu, 2023)
This research was conducted because there was data from the Ministry of Health (KEMENKES) in 2018 which explained that Bengkulu Province was recorded to have more than 45% of the proportion of dental and mouth problems. Data recapitulation of Bengkulu City Health Office recorded that in 2018 dental caries problems were 2,700 people, and data on Dental and Oral Health Service Activities of elementary school age children in Bengkulu City were 1,132 visits from 20 Puskesmas spread in 9 subdistricts in Bengkulu City. This study aims to determine the effect of Spinning Wheel Game media on knowledge about dental health of students of the Madrasah Ibtidaiyah Negeri 1 Bengkulu City. This study uses a Pre Experimental One Group Pre Test and Post Test Design research design. Samples amounted to 33 students Madrasah Ibtidaiyah Negeri 1 Bengkulu City, sampling using Proportional Random Sampling techniques, research analysis using the Paired Sample T-test. The results of the study were obtained the average knowledge before 3,4242 and after 9,1212. Paired Sample T-test test results obtained p value = 0,000 <0.05 which shows effect after being given health education with the Spinning Wheel game about dental health of Madrasah Ibtidaiyah Negeri 1 Bengkulu City. Spinning wheel game media can be used as a reference in providing health education about dental health in elementary school children. Keywords: Dental Health, Spinning Wheel Game, Knowledge